2022
DOI: 10.1088/2631-6331/ac826b
|View full text |Cite
|
Sign up to set email alerts
|

Integration of PCM as an external wall layer in reducing excessive heat of building walls

Abstract: Innovative building approaches, which take advantage of heat energy in buildings, have recently appeared as part of a global effort to save energy. Incorporating phase change material (PCM) into the building envelope helps in reducing energy consumption and regulating energy demand by managing the thermal inertia of designed PCM thermal characteristics. A study was conducted to assess the performance benefits provided by the latent heat of the concrete wall combined with PCM. This study focuses on developing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Ali et al [92] studied PCM/paint composite coated on the exterior of concrete panels. PCM paint composites offer a viable, free cooling strategy for building cooling applications.…”
Section: Free Coolingmentioning
confidence: 99%
See 2 more Smart Citations
“…Ali et al [92] studied PCM/paint composite coated on the exterior of concrete panels. PCM paint composites offer a viable, free cooling strategy for building cooling applications.…”
Section: Free Coolingmentioning
confidence: 99%
“…Ali et al [92] studied PCM/paint composite coated on the exterior of concrete panels. The study indicated a significant decrease in the surface temperature of the walls by 9 • C. Moreover, it was found that the annual energy consumption could be reduced by an impressive 64.3%.…”
Section: Free Coolingmentioning
confidence: 99%
See 1 more Smart Citation
“…Most traditional external insulation composite systems fix the insulation material onto a wall through binders or anchoring parts and then establish a protective layer and a decorative layer outside the insulation layer [20]. This construction technology increases the construction period, and the construction quality is difficult to guarantee, so there are certain hidden dangers [21].…”
Section: Introductionmentioning
confidence: 99%